Foliar Application of Several Nitrogen Sources as Fertilisers to Tempranillo Grapevines: Effect on Wine Volatile Composition - Rubio-Bretón, P.; Gutiérrez-Gamboa, G.; Pérez-Álvarez, E.P.; Santamaría, P.; Garde-Cerdán, T. (South African Journal of Enology and Viticulture, 2018)
Foliar nitrogen applications to the vineyard make it possible to improve grape and wine phenolic and amino acid concentration. However, to our knowledge, there is little information about their impacts on the volatile composition of wine. Therefore, the aim of this work was to evaluate the effects of the application of several nitrogen sources in Tempranillo vineyards on wine volatile composition during the first season. Subsequently, two dosages of phenylalanine and urea were applied to the vineyard with the aim of evaluating their effect on wine volatile composition. The results show that the different nitrogen sources applied to the grapevines during the first season did not affect higher alcohols, fatty acids, esters and other volatile compounds in the wines. The two dosages of phenylalanine and urea applied to the vineyard during the second vintage barely affected wine volatile composition. Consequently, this study shows that foliar nitrogen treatments in vineyards did not modify the wine aromatic profile.